2022
DOI: 10.1186/s42269-022-00850-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and bioactivities of Melaleuca alternufolia essential oil and its main constituents against Spodoptera littoralis (Boisaduval, 1833)

Abstract: Background Spodoptera littoralis is mostly controlled by the use of synthetic insecticides. Nonetheless, the use of these insecticides causes a slew of issues. On this pest, the antifeedant activity of Melaleuca alternifolia essential oil (EO) and its two principal components was investigated. Results The gas chromatography–mass spectrometry (GC/MS) analysis revealed that the M. alternifolia EO was composed of eleven compounds. Terpinen-4-ol (40.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Our results for growth inhibitory activities of γ-terpinene are supported by another study conducted by Abdelgaleil et al 55 , where they reported terpenes and phenylpropenes to inhibit the growth of S. littoralis larvae. The decrease in larval growth index after treatment with Melaleuca alternifolia (Maiden and Betche) Cheel and its main constituents, terpinene-4-ol and γ-terpinene in S. littoralis larvae was also observed by Ismail et al 56 . El-Minshawy et al 44 also reported reduction in pupation and adult emergence when second instar larvae of peach fruit fly, Bactrocera zonata (Saunders) were treated with monoterpenes viz.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our results for growth inhibitory activities of γ-terpinene are supported by another study conducted by Abdelgaleil et al 55 , where they reported terpenes and phenylpropenes to inhibit the growth of S. littoralis larvae. The decrease in larval growth index after treatment with Melaleuca alternifolia (Maiden and Betche) Cheel and its main constituents, terpinene-4-ol and γ-terpinene in S. littoralis larvae was also observed by Ismail et al 56 . El-Minshawy et al 44 also reported reduction in pupation and adult emergence when second instar larvae of peach fruit fly, Bactrocera zonata (Saunders) were treated with monoterpenes viz.…”
Section: Discussionsupporting
confidence: 57%
“…The post-ingestive toxic effects of γ-terpinene on the larvae of Z. cucurbitae were evident from the altered nutritional parameters i.e., decreased larval weight gain, food assimilated with respect to control, and mean relative growth rate. Ismail et al 56 also reported that M. alternifolia and its main constituents, terpinene-4-ol and γ-terpinene significantly reduced the feeding efficiency of S. littoralis larvae. They too observed a decline in weight gain and relative growth rate of the larvae.…”
Section: Discussionmentioning
confidence: 95%
“…Traditional peppermint oil and eugenol formulations showed insecticidal toxicity. Secondary metabolites of EOs are responsible for their insecticidal activities (Ismail et al, 2022). major chemical components like (Eucalyptol, D-menthone, , Menthol, γ-Terpineol)found as major components of peppermint oil) are responsible for the insecticidal activity (Adupa and Kagoya, 2018;Fouad et al,2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In his study, Abdel-Razik and Mahmoud (2017) mentions that jojoba oil has toxic effects, alter the feeding and egg-laying behavior of insects. As well, Ismail and Shaker (2014) reports a 76% of mortality using jojoba oil against the Immature stages of Spodoptera littoralis. It is recommended to evaluate the jojoba extract by itself to determine its ixodicide effect.…”
Section: Discussionmentioning
confidence: 95%